2014
DOI: 10.1007/s11033-014-3552-4
|View full text |Cite
|
Sign up to set email alerts
|

Apelin/APJ system: a promising therapy target for hypertension

Abstract: Apelin is a recently described endogenous peptide and its receptor APJ, is a member of the G protein-coupled receptors family. Apelin and APJ are widely distributed in central and peripheral tissues exert important biological effects on cardiovascular system. Recent studies have suggested that apelin/APJ system involves in decreasing the blood pressure and have a close relationship with hypertension, presumably, pathophysiology of hypertension as well. Such as, apelin/APJ system may be concerned in hyperfuncti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 93 publications
0
37
0
Order By: Relevance
“…At the early stage of cardiomyopathy, myocardial hypertrophy is a compensatory function, but ultimately, this can lead to heart failure and has become a significant independent risk factor of cardiovascular disease [47]. At present, myocardial hypertrophy occurs mainly due to mechanical load [1][2][3] and neurohumoral factors [4][5][6]. The earliest hemodynamic effect in the pathogenesis of myocardial hypertrophy has been identified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the early stage of cardiomyopathy, myocardial hypertrophy is a compensatory function, but ultimately, this can lead to heart failure and has become a significant independent risk factor of cardiovascular disease [47]. At present, myocardial hypertrophy occurs mainly due to mechanical load [1][2][3] and neurohumoral factors [4][5][6]. The earliest hemodynamic effect in the pathogenesis of myocardial hypertrophy has been identified.…”
Section: Discussionmentioning
confidence: 99%
“…Apelin-13 that acts as a mature apelin peptide, is the most commonly studied and has comparable affinity and agonist activity with the native apelin receptor in human tissues [3]. Apelin-13 is the predominant apelin isoform in human cardiac tissue [4] and plays a protective role in myocardial contraction, blood pressure regulation [5,6], myocardial injury [7], and so on. In addition to its protective role [8][9][10], apelin-13 promotes vascular smooth muscle cell (VSMC) proliferation [11][12][13] and endothelial cell (EC) adhesion [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…It was discovered in 1993 via homology cloning [164,165] . Apelin-13/APJ system has been identified as a potential therapeutic target for hypertension [166] and atherosclerosis [167] . Our laboratory has demonstrated that apelin-13 induced proliferation of vascular smooth muscle cells [66,168] and rat bone marrow-derived mesenchymal stem cells [169] through the Jagged-1/Notch3, cyclin D1 and AKT/ GSK3ÎČ/cyclin D1 pathways.…”
Section: Endoplasmic Reticulum Stress Is Involved In the Development mentioning
confidence: 99%
“…On the one hand, vascular endothelial shear stress, oxidative stress, inflammation and other factors can alter apelin expression; on the other hand, apelin has an impact on insulin sensitivity and cardiovascular function, exerting anti-inflammatory and antioxidant effects, acting as an adipokine (102). In addition, the overproduction of ROS can lead to a series of inflammatory reactions, and apelin can regulate the production of ROS; thus,there is a close link between apelin, oxidative stress and inflammation.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%